Business Model Transformation and Information Technology Use on the Quality of Accounting Information Systems in MSMEs in Indonesia - Lucky Mahesa Yahya (Westscience Press, 2024)
This research investigates the impact of business model transformation (BMT) and information technology utilization (ITU) on the quality of accounting information systems (QAIS) in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A quantitative approach is employed, with data collected through a survey of MSMEs across various industries. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) is used for data analysis. The findings reveal significant positive relationships between BMT, ITU, and QAIS. Business model transformation and IT utilization are found to significantly enhance the quality of accounting information systems in Indonesian MSMEs. These results highlight the importance of innovative business practices and effective technology adoption in improving financial management processes within MSMEs, providing valuable insights for practitioners, policymakers, and researchers.